M.M. Hala: Memoirs of an Umkhonto WeSizwe Cadre - Hala, Mzimasi Mike (Rhodes University, Faculty of Humanities, Institute of Social and Economic Research)
Born in Komani (Queenstown) in 1959 and detained for Congress of South African Students (COSAS) activities while still at school, Mzimasi Mike Hala departed South Africa via Swaziland in 1981 and joined uMkhonto WeSizwe (MK). Trained in Angola, Cuba and East Germany, he commanded Cacuso camp in Angola, until redeployed to South Africa in 1987 to work underground in Venda and Cape Town. Following the unbanning of the liberation movements in 1990, he was appointed Commander of MK's Transkei Region, where he was in charge of Chris Hani's personal security. For reasons of space, the memoir does not proceed beyond his integration into the South African National Defence Force (SANDF) with the rank of Lieutenant-Colonel and second-in-command of SANDF Group 46 in Mthatha. Besides its value as a primary source of previously undocumented information, the thesis seeks to bridge the gap between the academic literature on MK and the lived experience of MK soldiers. Having considered both the academic literature and the published MK memoirs in Chapter One, the thesis refers back to the literature in narrative chapters Two to Five. Consolidating its findings in its conclusion, the final chapter is divided into three sections: the political culture of MK, MK gender dynamics and the consequences of the political merger of the "exiles," including MK, and the "inziles" who subsequently came to dominate the ANC.
Keywords: African National Congress; Umkhonto we Sizwe (South Africa); Anti-apartheid movements -- South Africa; Anti-apartheid activists -- South Africa; South Africa Politics and government 1948-1994; Hani, Chris, 1942-1993; Holomisa, Bantu, 1955-; Bisho massacre